Alice in Wonderland syndrome: “Who in the world am I?” - Joseph Bruno Bidin Brooks; Fabio César Prosdocimi; Pedro Banho da Rosa; Yara Dadalti Fragoso (Arquivos de Neuro-Psiquiatria)
ABSTRACT Alice in Wonderland syndrome (AIWS) is a paroxysmal, perceptual, visual and somesthetic disorder that can be found in patients with migraine, epilepsy, cerebrovascular disease or infections. The condition is relatively rare and unique in its hallucinatory characteristics. Objective: To discuss the potential pathways involved in AIWS. Interest in this subject arose from a patient seen at our service, in which dysmetropsia of body image was reported by the patient, when she saw it in her son. Methods: We reviewed and discussed the medical literature on reported patients with AIWS, possible anatomical pathways involved and functional imaging studies. Results: A complex neural network including the right temporoparietal junction, secondary somatosensory cortex, premotor cortex, right posterior insula, and primary and extrastriate visual cortical regions seem to be involved in AIWS to varying degrees. Conclusions: AIWS is a very complex condition that typically has been described as isolated cases or series of cases.